THE EXISTENCE OF AJHERU' CABBIH IN THE CULTURE OF THE PENDALUNGAN COMMUNITY IN EAST JAVA - Arifullah, Muhammad; H., Levi Febrianing; Amalia, Nur Ismi; Nisa’, Ayu Khotimatun; Tjahyadi, Indra (Program Studi Bahasa Inggris, Universitas Panca Marga, 2023)
Pendalungan is a unique community. This uniqueness is caused by the hybrid cultural construction of the Pendalungan people. Therefore, it is relevant to carry out cultural research in the Pendalungan community. The object of this research is the Ajheru' Cabbih salvation tradition found in the Pendalungan Probolinggo community. The method used in this research is a descriptive qualitative method. Based on research conducted, it was found that Ajheru' Cabbih is the name of a ritual carried out by the Kedungrejo people before the first chili harvest. This ritual is meant to bring a successful harvest and blessings. The Ajheru' Cabbih tradition has been passed down from generation to generation and is characterized by various elements such as time, place, tools used, and the person who performs the ritual. Ajheru' Cabbih is not well known outside Kedungrejo, but this tradition still survives or has its existence to this day.